THE UKRAINIAN SHOOTING OF THE STARS: VASYL CHUMAK. - Лагетко, В. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The beginning of XX-th century. February revolution of 1917 in Russia and its significance for Ukraine. Vasyl Chumak as a poit and his social activity. Russian chauvinism: Bolsheviks and white quards interrupt Ukrainian independence. The first defenders of Ukrainian independence and their tragic fate.